EDUCATE THE COMMUNITY IN MALANG DISTRICT ON THE IMPLEMENTATION OF CLEAN AND HEALTHY LIVING BEHAVIOURS - Purwanza, Sena Wahyu; Wicaksono, Kurniawan Erman; Febriani, Reny Tri; Harningtyas, Sismala (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: Lack of knowledge influences a person's behavior, including clean and healthy living behavior. Implementing Clean and Healthy Living Behavior is a form of action that is useful for helping the community to recognize, know, and overcome problems that occur to individuals in the household setting. Most of the illnesses that occur in the community are caused by unhealthy behaviours that can be prevented by living clean and healthy. The purpose of the activity is to increase knowledge and empower communities to become self-sufficient in the area of health through the application of the principles of clean and healthy lifestyles. Methods: The programme used health education and discussion. This activity began with a pretest on knowledge of healthy living behaviour in the household, and was evaluated with a posttest on 80 health cadresattending the health education activity. It will be evaluated in several stages, with an initial, process and final evaluation. Descriptive stats were used to analyse the data. Results: The respondents were mostly aged 31-40 (45%), female (67.5%), and had equal high school education (32.5%). Most were self-employed (58.75%). Health education showed a difference in community ⁃ knowledge of healthy living. The p-value < 0.001, showing a significant difference in community knowledge of healthy living habits. Conclusion: The level of knowledge after the health education has been given is higher than that before the education. Education to improve knowledge and practice of clean and healthy lifestyles in communities is a continuous process that has a strong impact on healthy lifestyles in communities, especially in families. Therefore, continuous and targeted education is very important for awareness and health behavior change.